Analisis Penegakan Hukum dalam Perspektif Sistem Peradilan Pidana Berlandaskan Nilai-Nilai Pancasila - Prameswari, Resita Nanda (Philosophiamundi, 2025)
This article analyzes the effectiveness of child protection policies in addressing violence cases by combining normative and empirical approaches. The normative approach examines the existing legal framework, including the Child Protection Law, its implementing regulations, and relevant academic literature, particularly the works of Z. Hasan, while the empirical approach is carried out through interviews with the Legal and Human Rights Service Clinic of the Faculty of Law, UNS, which directly assists in cases of violence against children. The findings reveal a gap between legal norms and actual practice, particularly regarding limited public understanding, insufficient access to assistance, restricted capacity of law enforcement officers, and the risk of revictimization. Empirical evidence further shows that legal and psychosocial assistance services remain unevenly distributed, resulting in suboptimal child protection outcomes. The article concludes that strengthening institutional assistance capacity, enhancing public legal literacy, and developing more responsive reporting services are necessary, and recommends future research on integrating reporting technologies to improve early detection of violence against children